Perception of Child Prostitution in Some Selected Towns in the Western Region of Ghana - Taahiru-Swallah, Nasibatu (University of cape Coast, 2021)
Child prostitution, involves commercial exploitation. This study explored the factors that contribute to child prostitution in the Western Region of Ghana. The research employed both qualitative and quantitative research. Descriptive correlational survey design, snow ball, purposive sampling technique and structured interview schedules were used to select one hundred and three (103) respondents out of which thirty (30) girl - prostitutes were selected for in-depth interview. Frequencies, percentages, measures of central tendency and variation were used to describe relationships among variables. The results from the study revealed that 71.8% of the respondents started prostitution between 16 -17 years whiles 28.2% started between 12-15 years. Most of the respondents had had formal or non-formal education. However, those above eighteen were mostly JHS graduates who could not continue to the Senior High School (SHS) due poverty. Those who managed to learn a trade cited lack of start-up capital to start their own businesses as the main cause for entering into prostitutions. A greater proportion of the respondents lived alone in non-residential areas, slums and brothels without any parental or guardian support. Majority of the girls, 95.1%, do not stay with both parents, 25.2% of the girls’ parents are currently either divorced or 36.9% are separated. However, among the three factors leading and sustaining child prostitution, the economic factors were more prevalent. Recommendation such as stability of the family, parental control and financial support for parents from the state through Non Governmental Organizations and state agencies such as the livelihood empowerment program, improve girls’ retention in school were given on mitigating the phenomenon of child prostitution.
xvii,255p:,ill
Keywords: Commercial; Exploitation; Girls; Parents; Prostitution